Approaching “highly sensitive person” as a cultural concept of distress: a case-study using the cultural formulation interview in patients with bipolar disorder - Ioannou, Michael; Olsson, Sofia; Bakken Wold, Ane; Dellepiane, Marzia; Steingrímsson, Steinn (Frontiers in Psychiatry, 2023)
Psychiatric patients may refer to concepts neither medically accepted nor easily understood to describe their experiences when seeking medical care. These concepts may lie outside the clinician's cultural references and consequently hinder the diagnostic consultation. In the fifth version of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5), the clinical instrument Cultural Formulation Interview (CFI) was included. The CFI aims to facilitate the gathering and synthesis of culturally relevant clinical information. The notion of Cultural Concepts of Distress (CCD) was also introduced in DSM-5. The CCD include the subterms of the cultural syndrome, cultural explanation, and cultural idiom of distress. No previous study has used CFI for conceptualizing a cultural notion as a CCD. This study aimed to approach the cultural notion of being a highly sensitive person (HSP) in patients with bipolar disorder (BD) by applying the CFI. The cultural notion of HSP has garnered great interest globally, although scientific evidence is limited. No direct correlation between BD and HSP was hypothesized before or during the study process.In this case study, three patients with BD who reported being HSP were interviewed using the CFI. Furthermore, the applicability of the CCD was examined based on the outcomes of the CFI using an interpretive approach.All three patients reported that the CFI facilitated the clinical consultation, and in one of the cases, it may also have increased the treatment engagement. Based on the synthesis of the CFI outcomes in these illustrative cases, HSP could be understood as a cultural syndrome, a cultural explanation, and a cultural idiom of distress.By applying a person-centered perspective, CFI was used for the conceptualization of a cultural notion as a CCD (i.e. HSP in our study). Moreover, the cases highlight the complexity of illness insight in BD as a medical phenomenon when patients' illness perspectives are taken into consideration. Future studies need to further examine the clinical relevance of the CFI in the management of BD.